(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Pain is the most common symptom; it is universally accepted as a signal of disease that brings the patient to a physician’s attention. It is a sensation in which additional factors like mental or spiritual distress can cause the same overarching sensation as a physical damage. Anxiety is a common side effect of any pain, whether mild or severe. It interferes with the patient’s daily routine. Patient gets apprehensive or concerned about getting pain relief. It is generally known that NSAIDs can have serious side effects, which are mostly attributed to their underlying mechanisms of action. NSAIDs like indomethacin, ibuprofen, diclofenac, naproxen, aspirin, causes damaging action upon the stomach and intestine due to their acidic nature. While the selective COX-2 inhibitors cause significant adverse effects in the renal and cardiovascular systems, possibly more serious than those caused by conventional NSAIDs. Leech therapy or Jalaukavacarana, universally accepted around the globe, is an integral part of Ayurvedic medicine especially Panchakarma. Although not directly indicated for pain-management in Ayurveda texts, various studies have identified the presence of analgesic enzymes in leech’s saliva that can be effective in pain management in musculoskeletal disorders. So purpose of this article is reduce the use of NSAIDS and avoid there adverse effect and use new emerging Ayurvedic methods.